Exploring The Relation Between Stress and Knowledge of Risk Factors Among the Peptic Ulcer Patient at Ims & Sum Hospital, Bhubaneswar, Odisha, India - Mahuri, Brajendra; Puhan, Kabita; Mohapatro, Puspanjali; Mohapatra, Nirupama; Hota, Jyotshnamayee; Sahoo, Sushrita (Journal of Neonatal Surgery, 2025)
Peptic ulcer disease (PUD) is a common global health issue, often leading to serious complications like gastrointestinal bleeding and perforation, which are associated with high morbidity and mortality. This study aimed to assess stress levels and knowledge about PUD among patients, and to examine the association between stress and selected socio-demographic variables. A non-experimental survey was conducted using purposive sampling of 70 patients at IMS & SUM Hospital, BBSR, Odisha. Data were collected through interviews using the Sheldon Cohen Stress Scale and a structured questionnaire. Results showed that 78.51% of patients had moderate stress, 4.28% had high stress, and the mean stress score was 17.5. Regarding knowledge, 47.14% had poor knowledge, 38.57% average, and 14.28% good. While most socio-demographic variables showed no significant association with stress, education and religion were found to be significant. The study concluded that PUD patients generally experience moderate stress and have low levels of knowledge about the disease.